Correlation between Gas Distribution and Severity of Hepatic Portal Venous Gas - Motonari, Haruka; Matsumura, Toshinobu; Koami, Hiroyuki; Ishimine, Tomonari; Isa, Tsutomu; Kameyama, Shinichiro; Shirai, Tomoko; Taniguchi, Haruki; Nagamine, Yoshitetsu; Kohakura, Fumiko (Nippon Shokaki Geka Gakkai zasshi, 2013)
Although hepatic portal venous gas (HPVG) is considered to have poor prognosis, there have been recent reports on a number of conservatively treated cases. However, few studies have reported on the cause of HPVG, its pattern of progression, or its relationship with severity. We hypothesized that the distribution of HPVG correlates with severity and we conducted a retrospective review of 32 patients given a diagnosis of HPVG based on multi-dimensional computed tomography MDCT between August 2008 and December 2011. Patients were divided into two groups based on the area of gas distribution as follows: Group L (left lobe; 15 patients) and Group LR (both lobes; 17 patients). Data collected included demographics, clinical characteristics, MDCT findings, presence of bowel necrosis, and outcome. The chi-square test, Fischer’s exact test and Student’s t-test were used to compare variables. The groups were similar with regard to age, gender, symptoms, clinical findings, vital signs, and laboratory data. MDCT findings revealed that Group LR had significantly more cases than Group L of gastroduodenal dilatation (82.4% vs. 46.7%; P=0.040), small intestine dilatation (94.1% vs. 53.3%; P=0.011), pneumatosis intestinalis (100% vs. 46.7%; P<0.001) and main portal vein gas (70.6% vs. 33.3%; P=0.035). No respective significant differences in the number of operations performed (26.7% vs. 41.2%; P=0.314), presence of intestinal necrosis (33.3% vs. 52.9%; P=0.265), or mortality (53.3% vs. 52.9%; P=0.982) were found between group L and group LR. No significant correlation was confirmed between the distribution of HPVG and clinical severity, however, Group LR was considered to be more severe pathologically than Group L.